The price of civilization : reawakening American virtue and prosperity - Sachs, Jeffrey (New York : Random House Trade Paperbacks, 2012)
Offers a diagnosis of the country's economic ills and argues that Americans can restore the virtues of fairness, honesty, and foresight as the foundations of national prosperity.
"With a new preface by the author"--Cover.
Originally published in hardcover version by Random House in 2011.
Includes bibliographical references (p. 270-307) and index.
Keywords: Environmental responsibility -- United States; Social responsibility of business -- United States; United States -- Economic conditions -- 2009-; United States -- Economic policy -- 2009-; United States -- Politics and government -- 21st century